2020
DOI: 10.1007/s11356-020-09277-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oxygen limitation on the enrichment of bacteria degrading either benzene or toluene and the identification of Malikia spinosa (Comamonadaceae) as prominent aerobic benzene-, toluene-, and ethylbenzene-degrading bacterium: enrichment, isolation and whole-genome analysis

Abstract: The primary aims of this present study were to evaluate the effect of oxygen limitation on the bacterial community structure of enrichment cultures degrading either benzene or toluene and to clarify the role of Malikia-related bacteria in the aerobic degradation of BTEX compounds. Accordingly, parallel aerobic and microaerobic enrichment cultures were set up and the bacterial communities were investigated through cultivation and 16S rDNA Illumina amplicon sequencing. In the aerobic benzene-degrading enrichment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 53 publications
1
20
0
Order By: Relevance
“…Regarding metabolic potentials of strain D2P1 T it was found that it had a phenol-degradation gene cluster in its genome encoding for a multicomponent phenol-hydroxylase system and for a complete meta-cleavage pathway (data not shown). This cluster was most probably responsible for the benzene-degrading ability of strain D2P1 T , similarly as it was reported in the case of other members of the family Comamonadaceae [14]. Regarding the p-and m-xylene-degrading ability of strain D2P1 T , a large gene cluster (~28 kbp) was found encoding for all of the genes (e.g.…”
supporting
confidence: 79%
See 2 more Smart Citations
“…Regarding metabolic potentials of strain D2P1 T it was found that it had a phenol-degradation gene cluster in its genome encoding for a multicomponent phenol-hydroxylase system and for a complete meta-cleavage pathway (data not shown). This cluster was most probably responsible for the benzene-degrading ability of strain D2P1 T , similarly as it was reported in the case of other members of the family Comamonadaceae [14]. Regarding the p-and m-xylene-degrading ability of strain D2P1 T , a large gene cluster (~28 kbp) was found encoding for all of the genes (e.g.…”
supporting
confidence: 79%
“…The Siklós site is one of the best-characterized petroleum hydrocarbon contaminated environment in Hungary (45° 51′ 25.8″ N 18° 17′ 32.3″ E) [13], contaminated mainly with xylenes. To isolate strain D2P1 T , a fully aerobic (~7–8 mg l −1 dissolved O 2 ) enrichment was set up in 100 ml crimp-top serum bottles, which contained 45 ml of a mineral salt medium supplemented with vitamins (MSV medium) as described earlier [14], 5 ml groundwater sample and 1 mM para -xylene as sole source of carbon and energy. After consecutive seven transfers, 1 ml enrichment culture was serially diluted with 0.85 % (w/v) sterile saline solution.…”
Section: Full-textmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxic enrichment cultures were set up in triplicates, named AER1, AER2, and AER3, using 45 mL of freshwater media dispensed in 100 mL crimp-sealed serum bottles ( Révész et al, 2020a ). Biofilm samples were collected from a gasoline contaminated groundwater well ( Benedek et al, 2016 ), of which 1 g (wet weight) was mixed with 99 mL of physiological saline solution.…”
Section: Methodsmentioning
confidence: 99%
“…Oxic enrichment cultures were set up in triplicates, named AER1, AER2, and AER3, using 45 mL of freshwater media dispensed in 100 mL crimp-sealed serum bottles (Révész et al, 2020a). Biofilm samples were collected from a gasoline contaminated groundwater well (Benedek et al, 2016), of which 1 g (wet weight) was mixed with 99 mL of physiological saline solution.…”
Section: Enrichment Culturesmentioning
confidence: 99%